2008
DOI: 10.1007/s11259-008-9188-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-enzymatic antioxidant status and modulation of lipid peroxidation in the muscles of Labeo rohita by sub lethal exposure of CuSO4

Abstract: Xenobiotics-mediated environmental stress is an important determining factor in the maintenance of fish health as fishes are frequently exposed to such components. Increasing evidences indicate that acute and chronic xenobiotic exposure modulates ROS production, suppresses immune response and increase the incidence of fish diseases. In the present context an attempt has been made to study the in vivo effect of different concentrations of CuSO(4) (0.5, 1.00 or 2.00 ppm) on lipid peroxidation (an index of oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…As evidence, inhibition of liver GSH was seen in three spined sticklebacks (Gasterosteus aculeatus) upon exposure to copper sulfate (Sanchez et al, 2005). In support of this study, Jena et al, 2009 showed the depletion of muscle GSH after copper sulphate exposure. The significant reduction in the GSH level is mainly due to direct copper interference with GSH synthesis by inhibition of glutathione reductase.…”
Section: Glutathione (Gsh)supporting
confidence: 77%
“…As evidence, inhibition of liver GSH was seen in three spined sticklebacks (Gasterosteus aculeatus) upon exposure to copper sulfate (Sanchez et al, 2005). In support of this study, Jena et al, 2009 showed the depletion of muscle GSH after copper sulphate exposure. The significant reduction in the GSH level is mainly due to direct copper interference with GSH synthesis by inhibition of glutathione reductase.…”
Section: Glutathione (Gsh)supporting
confidence: 77%
“…Gravato et al (2006) attribute the depletion of GSH to direct copper interference with GSH synthesis, inhibition of glutathione reductase, and the participation of GSH as a substrate in detoxification reactions. The depletion of GSH in fish muscle after copper sulphate exposure has also been reported (Jena et al, 2009).…”
Section: Coppermentioning
confidence: 81%
“…An increased ASC pool and ASC/DHA value is an indicator of the adaptive response to limit the oxidative damage in fish [46], [85]. The high levels of reduced [ASC] in response to HEA connote an advantage for the carp and goldfish to resist oxidative stress.…”
Section: Discussionmentioning
confidence: 99%